Propriedades físicas do solo e a estabilidade das encostas na Serra do Mar, Sudeste do Brasil - Coelho, Rebeca Durço; Gramani, Marcelo Fischer; Vieira, Bianca Carvalho (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2022)
Soil physical properties play an important role in landslide rupture mechanisms, since changes in soil texture, structure, and porosity can affect slope permeability. This study characterized a granitic weathering profile and assessed the changes in the properties of the materials related to the main mechanisms that trigger landslides. The study identified three layers with distinctive particularities in macromorphological and micromorphological terms: mature residual soil (well-developed), young residual soil (saprolitic soil), and saprolite. Morphological characterization was carried out in addition to textural analysis, and soil porosity and saturated hydraulic conductivity (Ksat) tests. The weathering profile presented clear differences in morphology, pore size and soil texture, which  could indicate distinct weathering grades. The results suggested that continuous heavy rainfall could contribute to the increase in pore-water pressure between mature residual soil and young residual  soil, favoring the occurrence of slope failure.